ANALISIS PERHITUNGAN TARIF KAMAR RAWAT INAP RUMAH SAKIT DENGAN METODE ACTIVITY BASED COSTING SYSTEM - Ulumia, Miftachul; Made, Anwar; Yogivaria, Dony Wirshandono (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2020)
The purpose of this study was to determine the amount of hospitalization fare using the Activity Based Costing method approach at Wijaya Kusuma Lumajang Hospital. As well as analyzing a large comparison of inpatient room rates between the Activity Based Costing System method and the Traditional methods that have been applied by Wijaya Kusuma Lumajang Hospital so far. This research is a descriptive study with a quantitative approach. Data collection techniques used in this study were documentation, observation, and interviews. Data analysis method used is to calculate the cost of inpatient services based on traditional cost accounting, calculate the cost of inpatient rooms based on the Activity Based Costing method, where the results of the calculation of the two methods will be compared to the cost of inpatient rooms. The results of the calculation of the cost of hospitalization at Wijaya Kusuma Lumajang Hospital using the Activity Based Costing System found a lower tariff difference for VIP 1 room Rp31,997.07, while higher rates occurred in VIP Room 2 with a difference of Rp56,570 , 68,, Class 1 Rp.193,765.10, Class 2 Rp.447,881.33 and Class 3 Rp.79,375.90.